Respuesta :

[tex]36x^4 - 25=(6x^2)^2-5^2=(6x^2-5)(6x^2+5)[/tex]

The factored form of the equation [tex]36x^{4}-25[/tex]  is  [tex](6x^{2} +5)(6x^{2} -5)[/tex].

Factorisation

What is factorisation?

Instead of expanding the bracket and turning the equation into a product of components that cannot be further reduced, factorisation involves decreasing the bracket of a quadratic equation.

Formula used in factorisation:

[tex]x^{2} -y^{2} =(x+y)(x-y)[/tex]

Factorise the given equation:

The given equation is,

= [tex]36x^{4}-25[/tex]

The above equation can be written as,

= [tex]6^{2} {(x^{2} )^{2} }-5^{2}[/tex]

= [tex](6x^{2} )^{2} -5^{2}[/tex]

By using factorisation equation,

= [tex](6x^{2} +5)(6x^{2} -5)[/tex]

Therefore, the factorisation of the equation  [tex]36x^{4}-25[/tex] is [tex](6x^{2} +5)(6x^{2} -5)[/tex].

To know more about how to calculate the roots of the quadratic equation by using the factorisation formula, here

https://brainly.com/question/24031074

#SPJ2